Pomegranate Peel Extract Alters the Microbiome in Mice and Dysbiosis Caused by Citrobacter Rodentium Infection (P20-043-19). (13th June 2019) - George, Nadja; Cheung, Lumei; Luthria, Devanand; Santin, Monica; Dawson, Harry; Bhagwat, Arvind; Smith, Allen
Abstract: Objectives: We previously showed that a pomegranate peel extract (PPX) reduced the pathogenicity of a Citrobacter rodentium ( Cr ) infection, an E. coli -like organism that infects mice and mimics many aspects of pathogenic E coli infections in humans. The purpose of this study was to evaluate the effect of PPX on the microbiome of uninfected and Cr -infected mice to determine if changes to the microbiome was associated with reduced pathogenicity. Methods: To evaluate the effect of PPX on the microbiome, mice were treated with water or PPX for 14 days and feces collected for analysis. In a second experiment, mice were treated with PPX for 14 days, feces collected, the mice infected with Cr and feces collected again at day 6 post-infection. Colon tissue was collected at day 12 post-infection for determining Cr load and histological analyses. DNA was isolated from the fecal samples and subjected to 16S rRNA gene sequencing to determine the microbial composition. Results: PPX treatment decreased the extent of Cr-induced colon damage. Differences in the composition of the microbiome were observed for untreated and PPX-treated mice with PPX mice having decreased diversity. PPX treatment decreased the Firmicutes/Bacteroidetes ratio by increasing Bacteroidetes and decreasing Firmicutes levels. The decrease in Firmicutes was driven by a large reduction in Lactobacillus . PPX-treatment increased the abundance of Proteobacteria and Verrucomicrobiae and decreased Actinobacteria. The relative abundance of Cr reached 22% in water-treated but only 5% in PPX-treated infected mice while the absolute numbers of Cr were similar between the two groups and this may have contributed to the reduced pathology in PPX-treated Cr -infected mice. Conclusions: PPX-treatment altered the microbiome making it more resistant to displacement by infection with Cr, thus reducing the percentage of the total microbiome that Cr occupied and this correlated with reduced colon pathology. These results show that the pomegranate peel contains compounds that have the potential to alter the host microbiome and pathology induced by an important class of food-borne enteric bacteria. Funding Sources: USDA Agricultural Research Service.